A cash-for-care scheme targeting children with disabilities in Turkey: Parent / caregiver perspectives - Avşaroğlu, Nazlı. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
A cash-for-care scheme targeting mainly families with at least one disabled member has become the central policy response to the care needs of persons with disabilities in Turkey’s welfare regime. This thesis explores how beneficiaries perceive this program by focusing specifically on caregivers of children with disabilities. In-depth semi-structured interviews were conducted with 16 caregivers of children with disabilities—four primary caregivers who have been receiving cash-for-care at the time of the research and four primary caregivers who have lost their benefits—in Istanbul’s Atasehir and Sultangazi districts between February and May 2016. The research reveals that although cash-for-care scheme has been widely welcomed by the informal caregivers, it has been perceived by the caregivers as a symbolic financial aid instead of a wage in exchange for their informal care work. In addition, cash-for-care beneficiaries that were included in this study perceive this scheme primarily as a financial support for poverty alleviation rather than a cash benefit in order to meet the special needs of their children with disabilities. While the introduction of a targeted cash-for-care allowance has signified an extension of state responsibility in social care, this thesis concludes that the program functions not as a care support scheme but as a social assistance scheme for the very poor.
Keywords: Children with disabilities -- Home care.; Chronically ill children -- Home care.